Ações possessórias e o fluxo de técnicas diferenciadas - Puppin, Bárbara Altoé (2019)
he present research is inserted in the thematic of the possessory actions and the flow of differentiated techniques foreseen in the Brazilian legal order, with the objective of verifying the possibility of the different possessory techniques compatibilization for the achievement of an efficient, adequate and timely judicial protection. For this, we examined the possession institute, in order to establish sufficient premises for the analysis of procedural law. Afterwards, a study was carried out on the procedural protection of tenure in the country's legal system, and then the typical possessory actions and their differentiated techniques were analyzed as provided for in the Code of Civil Procedure of 2015. In the end, it was verified that differentiated possessory techniques are only the provisional guardianship of new force and the limitation of horizontal cognition, which may pass between the atypical possessory actions, based on the procedural flexibility model adopted by the current procedural law, in order to draw the possessory procedure from the different techniques combination and adapt it to the material legal situation of the specific case. The research was developed through the hypothetical-deductive methodology and the documentary and bibliographical research technique, by qualitative approach and is linked to the research line, Constitutionality and Protection of Existential and Patrimonial Rights of the Post-Graduate Program in Procedural Law of the University Federal of Espírito Santo